2013
DOI: 10.1371/journal.pone.0071870
|View full text |Cite
|
Sign up to set email alerts
|

New Insights of Microsporidial Infection among Asymptomatic Aboriginal Population in Malaysia

Abstract: BackgroundStudies on microsporidial infection mostly focus on immunodeficiency or immunosuppressive individuals. Therefore, this cross-sectional study describes the prevalence and risk factors of microsporidiosis among asymptomatic individuals in Malaysia.Methods/FindingsFour hundred and forty seven stool samples were collected and examined for microsporidia after staining with Gram-chromotrope Kinyoun. Demographic, socioeconomic, environmental, and behavioral information were collected by using a pre-tested q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Co-infections of soil-transmitted helminth with a diversity of protozoa such as Giardia sp., Entamoeba spp., Blastocystis spp. and microsporidia with prevalence ranging from 15.0 to 22.2% have been observed [7] [9] . Multiparasitism has proven to increase anaemia, morbidity and reduce cognitive development in children [10] [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Co-infections of soil-transmitted helminth with a diversity of protozoa such as Giardia sp., Entamoeba spp., Blastocystis spp. and microsporidia with prevalence ranging from 15.0 to 22.2% have been observed [7] [9] . Multiparasitism has proven to increase anaemia, morbidity and reduce cognitive development in children [10] [12] .…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of microsporidian infections among immunocompromised patients was slightly higher compared with previous local studies. [8][9][10][11][12][13][14][20][21][22] Comparing the findings of the present study with studies from other countries showed that the prevalence was higher than for those reported in Spain (17%), 23 Czech Republic (15%), 24 and India (1.8%). 25 By contrast, studies in Iran reported a high prevalence of microsporidiosis (more than 30%) among immunocompromised hosts.…”
Section: Discussionmentioning
confidence: 43%
“…High prevalence rates were also reported in healthy aboriginal Malaysians in Southeast Asia (Shahrul Anuar et al. ) and in Pakistan on the Asian continent (Yakoob et al. ).…”
mentioning
confidence: 84%